PENENTU KINERJA UMKM OLEH DINAS PERDAGANGAN, KOPERASI DAN USAHA MIKRO KABUPATEN BOJONEGORO - Ferly Arvidia Anindita; Kustini Kustini (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are one of the holders of roles in Indonesia's economic growth. One of the active MSME sectors in Bojonegoro Regency is a food and beverage business in Bojonegoro Subdistrict with a small business scale. Small businesses have an important role in increasing the performance of MSMEs, namely through training and mentoring. This study aims to examine the effect of training and mentoring of the Department of Trade, Cooperatives, and Micro Enterprises on the performance of MSMEs in the Bojonegoro Regency. The research sample amounted to 91 food and beverage business actors in Bojonegoro Subdistrict with a simple random sampling technique. Data was collected through a research instrument in the form of a questionnaire. Testing the validity and reliability of the questionnaire was carried out first. In testing the hypothesis through the SEM PLS analysis method, it can be seen that the t-test, p-values, and original sample show that training and mentoring have a significant and positive influence on the performance of MSMEs, where the research hypothesis can be accepted. Based on the results of R2, 99% of MSME performance is influenced by training and mentoring.